Climate change, climatic disasters, and adaptation techniques: learnings from the lowlands of Nepal - Thagunna, Roshan Singh; Chhetri, Sagar Godar; Gautam, Deepak; Bhattarai, Diwakar; Thapa, Prakash Singh (Banko Janakari, 2022)
Nepal is experiencing inevitable consequences of changing climate. Rural communities are badly suffering from these implications. Meanwhile, the rural communities are trying to acclimatize through small–scale adaptation efforts. This study aims to analyze changes in temperature and rainfall trends, identify major climatic disasters, and document current adaptation measures being adopted by rural communities. For this study, we randomly selected 220 households from a total of 4,282 Households, and seven key informants for the questionnaire survey within the study area. Meteorological data from the nearest station were used to analyze changes in temperature and rainfall trends. The study revealed that both mean annual maximum and minimum temperature increased by 0.063 °C/year and 0.072° C/year respectively, between 1991 and 2020. Similarly, mean annual rainfall increased by 12.329 mm/year. Floods, droughts, landslides, hailstorms, and forest fires were major climate disasters experienced by the locals. The adverse impact perceived were loss of crop yield, decrease in water availability, an increase of mosquitoes, and a decline in sightings of the birds and waterfowls in the area. Embankment construction along rivers, changing cropping patterns and cultivation time, forest protection, and maintaining home gardens were major adaptation measures being practiced by the locals. We believe the findings of this study will be helpful for policymakers to develop strategies and programs for communities that will promote resilience against climate– induced disasters at a local level in the lowlands of Nepal.